Dewan Perwakilan Rakyat Dan Majelis Permusyawaratan Rakyat Dalam Proses Impeachment Presiden Abdurrahman Wahid - Bergas, Kukuh (Jurnal Hukum & Pembangunan, 2019)
As a country that uses presidential systems, Indonesia realizes that the role of the president as an executive is powerful. Therefore it is necessary to establish legal rules or supervisory institutions as a counterweight to avoid abuse of authority. The DPR and MPR are legislative institutions whose task is to oversee the performance of the president. If a suspected violation is found, the DPR may submit a proposal for the dismissal of the president. Indonesia's 4th President experienced this case, K. H. Abdurrahman Wahid is also known as Gus Dur, because he was considered to have committed a violation which could potentially lead to the collapse of democracy due to several large cases. Although this research is not the first to analyze this problem, this would provide a more comprehensive study on the removal of Indonesia’s president. Those decisions taken through the controversial legal bases would be analyzed from the perspective of legal, politic, and moral aspects.